Over-Expression of a 14-3-3 Protein From Foxtail Millet Improves Plant Tolerance to Salinity Stress in Arabidopsis thaliana - Liu, Jiaming; Jiang, Chengyao; Kang, Lu; Zhang, Hongchang; Song, Yu; Zou, Zhirong; Zheng, Weijun (Frontiers in Plant Science, 2020)
In plants, 14-3-3 proteins are recognized as mediators of signal transduction and function in both development and stress response. However, there are only a few preliminary functional researches in the C4 crop foxtail millet. Here, phylogenetic analysis categorized foxtail millet 14-3-3s (SiGRFs) into ten discrete groups (Clusters I to Ⅹ). Transcriptome and qPCR analyses showed that all the SiGRFs responded to at least one abiotic stress. All but one SiGRF-overexpressing (OE) Arabidopsis thaliana line (SiGRF1) exhibited insensitivity to abiotic stresses during seed germination and seedling growth. Compared with the Col-0 wild-type, SiGRF1-OEs had slightly lower germination rates and smaller leaves. However, ﬂowering time of SiGRF1-OEs occurred earlier than that of Col-0 under high-salt stress. Interaction of SiGRF1 with a foxtail millet E3 ubiquitin-protein ligase (SiRNF1/2) indicates that the proteinase system might hydrolyse SiGRF1. Further investigation showed that SiGRF1 localized in the cytoplasm, and its gene was ubiquitously expressed in various tissues throughout various developmental stages. Additionally, flowering-related genes, WRKY71, FLOWERING LOCUS T, LEAFY and FRUITFULL, in SiGRF1-OEs exhibited considerably higher expression levels than those in Col-0 under salinity-stressed conditions. Results suggest that SiGRF1 hastens ﬂowering, thereby providing a means for foxtail millet to complete its life cycle and avoid further salt stress.